Canada's position and participation in the early development of the International Monetary Fund, 1940-1943 - Scott, Thomas E. (My University, 1985)
This study focuses on Canada's involvement in the informal discussions that ultimately led to the creation of the International Monetary Fund, These discussions, which involved three main participants, Canada, the United Kingdom and the United States, took place during 19^0-19^3 established the basic format of the plan used at the Bretton Woods conference in 1944. During the discussions of I940-I943, two proposals for an international financial organization, one British and one American, were considered. In part, the differences in the two proposals were owing to the differences in the British and American international financial situations. It was the task of Canadian officials to not only advocate the proposal that was beneficial to Canadian interests, but also to maintain Anglo-American cooperation. It is argued that the position taken by Canadian officials was based on past Csinadian trade and financial experiences, as well as on expectations of the postwar world. However, Canada needed "both Britain and the United States in her trade and financial network, hut this was not assured in either proposal. In fact, it often seemed as though Britain and the United States would not he a part of the same international financial organization. Moreover, there was also a fine line between achieving Anglo- American cooperation and being faced with an Anglo-American diktat, which Canadian officials had to deal with. Although Canadian officials considered either proposal an improvement over the situation that existed in the interwar period, they nevertheless believed that further benefits to Canada could be achieved through active Canadian participation throughout the informal discussions. With all of these considerations in mind, Canadian officials drafted a Canadian proposal which was presented in 1943.
Keywords: International economic relations History